The Effects of Patient Education on Psychological Status and Clinical Outcomes in Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Wu, Zugui; Zhu, Yue; Wang, Yi; Zhou, Rui; Ye, Xiangling; Chen, Zehua; Li, Congcong; Li, Junyi; Ye, Zixuan; Wang, Zhenbang; Liu, Wengang; Xu, Xuemeng (Frontiers in Psychiatry, 2022)
Background Rheumatoid arthritis (RA) is a common systemic inflammatory autoimmune disease. The disease has a serious impact on mental health and requires more effective non-pharmacological interventions. Objective This study aims to systematically evaluate the effectiveness of patient education on psychological status and clinical outcomes in rheumatoid arthritis. Methods This systematic review and meta-analysis was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed, Cochrane Library, EMBASE database, and Web of Science database were screened for articles published until November 2, 2021. Randomized controlled trials (RCTs) of patient education for RA were included. Outcomes measures included pain, physical function, disease activity, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), anxiety, depression, Arthritis Self-Efficacy (pain, other symptoms, total), and General health. For each outcome, standardized mean differences or mean differences and 95% confidence intervals (CIs) were calculated. Results A total of 24 RCTs (n = 2,276) were included according to the inclusion and exclusion criteria. Meta-analysis revealed a statistically significant overall effect in favor of patient education for physical function [SMD = −0.52, 95% CI (−0.96, −0.08), I2 = 93%, P = 0.02], disease activity [SMD = −1.97, 95% CI (−3.24, −0.71), I2 = 97%, P = 0.002], ASE (pain) [SMD = −1.24, 95% CI (−2.05, −0.43), I2 = 95%, P = 0.003], ASE (other symptoms) [SMD = −0.25, 95% CI (−0.41, −0.09), I2 = 25%, P = 0.002], ASE (total) [SMD = −0.67, 95% CI (−1.30, −0.05), I2 = 90%, P = 0.03], and general health [SMD = −1.11, 95% CI (−1.36, −0.86), I2 = 96%, P < 0.00001]. No effects were found for anxiety [SMD = 0.17, 95% CI (−0.64, 0.98), I2 = 82%, P = 0.68], depression [SMD = −0.18, 95% CI (−0.52, 0.15), I2 = 52%, P = 0.28], pain [SMD = −0.37, 95% CI (−0.80, 0.05), I2 = 89%, P = 0.08], and CRP [SMD = −0.27, 95% CI (−0.57, 0.02), I2 = 0%, P = 0.07]. Conclusions Patient education may be effective in improving clinical outcomes and psychological status in patients with rheumatoid arthritis. Considering the methodological limitations of the included RCTs, more high-quality and large-sample RCTs are needed to confirm this conclusion in the future. Systematic Review Registration http://www.crd.york.ac.uk/prospero, identifier: CRD42021250607.